Strategic entrepreneurship increase innovation, competition, employment, and economic development - Fakhraddin Maroofi, Alireza Takhtshahi (International Journal of Scientific Research and Management (IJSRM), 2017)
Strategic entrepreneurship is predicated on the combination of entrepreneurship and strategic management. Strategic entrepreneurship could be a new approach in management literature. Moreover, today's business world needs an orientation towards strategic entrepreneurship. Strategic entrepreneurship is a necessity for corporations to form most wealth. During this study, strategic entrepreneurship and strategic management are analyzed.